Advances in financial planning and forecasting. Vol. 11 - Lee, Cheng-Few. (Amsterdam ; London : JAI, 2003)
Contains ten papers, including: An Empirical Examination of The Intraday Return Volatility Process; The Valuation of New Product Introduction Under Uncertain Competition: A Real Option Approach; Earnings, Dividends, and Equity Value of Multinational Firms; Debt Covenant Violation and the Value Relevance of Accounting Information; and more.
Includes bibliographical references.
oif 31/08/15
Loan
Keywords: Corporations -- Finance; Business enterprises -- Finance; Business forecasting